USE OF ELEMENTS OF ETHNIC SCIENCE IN THE PROCESS TRAINING OF FUTURE ENGINEERS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2008)
The revival spiritual and moral is a necessity of time. In clause the conceptual principles of spiritual - moral education of the students by means of national knowledge are proved.
Keywords: humanitarian thinking; gumanitarizatsiya of maximum education; humanitarian values; gumanitarizatsiya of scientific process; humanitarian aspect; humanitarian process; universal values; educational process